Prediction of mining-induced seismicity and damage assessment of induced surface buildings in thick and hard key stratum working face: a case study of Liuhuanggou coal mine in China - Wang, Gaoang; Zhu, Sitao; Zhang, Xiufeng; Wen, Yingyuan; Zhu, Zhijie; Zhu, Quanjie; Xie, Liangfu; Li, Jiajie; Tan, Yi; Yang, Tao; Pu, Yuanyuan; Zhu, Chun (Frontiers in Earth Science, 2023)
The thick and hard key stratum working face are characterized by frequent mine tremors and significant ground tremors during mining, which seriously threaten the safety production of the mine. With (4-5)06 working face of Xinjiang Liuhuanggou Coal Mine as engineering background, using field investigation, microseismic monitoring and theoretical analysis, a mining-induced seismicity prediction method and damage assessment of surface buildings for thick and hard key stratum working face is proposed, which is based on the evolution characteristics of overlying strata spatial structure and the motion state of key stratum. The results of the study are as follows: (1) The magnitude of the risk of mining-induced seismicity occurrence is mainly related to the boundary conditions of working face, the thickness of key stratum, the distance from coal seam to key stratum, the height of over-lying strata spatial structure and the fracture step of key stratum. (2) The mining-induced seismicity energy contains the original accumulation elastic energy of key stratum, the transfer elastic energy of low rock strata and the accumulation elastic energy of gravity work. Based on this, the mechanical model of surface buildings damage induced by the release of mining-induced seismicity energy was established. The ground vibration damage boundary and vibration induction boundary under the action of strong mining-induced seismicity were proposed, and the service life of buildings when they reach the critical damage value under the action of 2 This is a provisional file, not the final typeset article frequent mining-induced seismicity was obtained. (3) The temporal and spatial distribution law of mining-induced seismicity activities in thick and hard key stratum working face is revealed. According to the results of micro-seismic monitoring, the "zonality" characteristics of the time series and the "transition" law of spatial distribution of mining-induced seismicity verified the reliability of the mining-induced seismicity prediction method. The research results provide a theoretical basis for predicting mining-induced seismicity and assessing the risk of induced disasters during the mining process of thick and hard key stratum working faces, and can provide technical support for mininginduced seismicity prevention and control and safety production in mines with similar conditions.